Development and application of analytical methodology with the combined use of gold nanoparticles and aptamers for the colorimetric detection of Pseudomonas aeruginosa - Schmitz, Fernanda Raquel Wust (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia Química, Florianópolis, 2022.